Talking across purposes [sic] in social investing: Standardising boundary objects in times of crisis - Morley, Julia (The British accounting review, 2025)
Boundary objects are ambiguous terms that are useful in enabling parties with different incentives, belief systems, or cultural commitments to collaborate. However, the misunderstandings that arise due to this ambiguity will eventually prompt the initiation of a process of standardisation intended to make the meanings of terms more precise to all parties, thereby enabling collaboration to continue. Existing theories of standardisation of boundary objects identify how meanings of terms are renegotiated during standardisation but do not refer to the effect of background conditions — stable or unstable — on this process. This study uses interview and documentary evidence to examine the standardisation of boundary objects between 2010 and 2023 in the UK market for social investment and identifies how this differed between the periods before and during the COVID-19 pandemic. The findings suggest that the process of standardisation of boundary objects is affected by the context in which it takes place, in particular, whether it occurs during periods of stability or during periods of instability.